How to Construct Super Edge-Magic Total Labeling of Theta Graph θ(2,b,c) - Mujtahid, Zainul; AN, M Salman; Hidayat, Amam Taufiq; Qausar, Haves; Zahara, Yulia (Universitas Tidar, 2024)
This research study and provide the property of super edge-magic total labelings of theta graph. Edge magic labeling on a graph is an injective function from to a subset of integers with the property that there is a positive integer such as for each . An edge-magic labeling is called super edge-magic total labeling if it satisfies . A graph is called (super) edge-magic total if it admits some (super) edge-magic total labeling. A theta graph is constructed by embedding the endpoints of three paths of length consecutive such that there are two vertices of degree three and the other of degree two. This study gave some conditions for such a super edge-magic total of theta graph. Based on this condition, this paper introduce some algorithms to apply and develop super edge-magic total labeling from some previous theta graphs.